Effectiveness of augmented reality application on critical thinking skills of elementary school students based on learning interest - Saki, Saki; Usodo, Budi; Santosa, Eka Budhi (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
Mathematics learning in elementary schools is still dominated by conventional methods such as lectures and the use of two-dimensional images, which do not support the development of critical thinking skills and students' spatial understanding. This challenge is increasingly relevant in the era of the Industrial Revolution 4.0, which demands the integration of technology in the learning process. This study aims to analyze the effect of the use of Augmented Reality (AR) on critical thinking skills and students' learning interest in learning spatial figures. The study used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group design. The sample consisted of 60 elementary school students in Banjarsari District who were divided into an experimental group (using AR) and a control group (conventional method). Learning lasted for four weeks, with three sessions per week. The research instruments included a critical thinking test based on Ennis's indicators and a Likert-scale learning interest questionnaire. The results of the analysis using the Shapiro-Wilk and Mann-Whitney U tests showed a significant difference between the experimental and control groups in the critical thinking posttest scores (p = 0.0076). The increase occurred in the aspects of clarification, inference, and argument evaluation. In addition, students' learning interest in the experimental group also increased, indicated by active involvement and higher motivation. In conclusion, using AR effectively improves students' critical thinking skills and learning interests. The implications of this study indicate that AR technology can be an innovative alternative to mathematics learning. The contribution of this study lies in the development of technology-based learning strategies to support the 21st-century skills of elementary school students.